Examinations and assessments in patients with a newly acquired spinal cord injury – retrospective chart analysis as part of a quality improvement project (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Examinations and assessments can be used to ensure good quality rehabilitation. Within the framework of a quality improvement project, the aims of the current analysis were: first, to analyse the time points of selected examinations and assessments in the rehabilitation process of patients with a newly acquired spinal cord injury. Second, to identify differences between the subgroups with different aetiologies, levels and completeness of spinal cord injuries. And third, to compare the examinations and assessments performed with the guideline recommendations and to use discrepancies as a starting point for a quality improvement project. METHODS In this retrospective chart analysis, adult patients with a newly acquired spinal cord injury who were admitted to a single specialised acute care and rehabilitation clinic for their first rehabilitation between December 2013 and December 2014 were included and assessed until discharge. The main objective was to assess the time to examinations or assessments after injury or hospital admission in comparison to the respective recommendations. Analyses were done using time-to-event analysis and represented graphically using Kaplan-Meier plots. RESULTS Of the 105 patients included in this study (median age 58 years, 29% female), 61% had a traumatic and 39% a non-traumatic spinal cord injury; 39% were paraplegic and 61% were quadriplegic; and 59% had a motor complete and 41% a sensor-motor incomplete spinal cord injury. The percentage of patients for whom the respective assessment or examination was performed and the percentage of these patients for whom it performed within the recommended time were: 90% and 71% for magnetic resonance imaging; 85% and 90% for computed tomography; 87% and 79% for the manual muscle test; 95% and 59% for the International Standards for Neurological Classification of Spinal Cord (ISNCSCI); 84% and 50% for electrophysiological assessment; 73% and 90% for urodynamic testing; and 49% and 53% for lung function testing. CONCLUSIONS Our data suggest a relevant gap between recommendations and clinical routine for time to some assessments after spinal cord injury. Within the framework of a quality improvement project, the next steps should be to build a national and international consensus on specific time frames for examinations and assessments in patients with a newly acquired spinal cord injury and thereafter, to develop an institutional implementation strategy.